DEVELOPMENT OF A SCRATCH-BASED EDUQUIZ ON THE CLASSIFICATION OF LIVING ORGANISMS TO IMPROVE THE LEARNING OUTCOMES OF 7TH GRADE STUDENTS - Auliyaur, sayyidah; Syamsudin, Ahmad (Program Studi Pendidikan IPA FIP Universitas Hasyim Asy'ari, 2026)
This study aims to develop an educational game called “Eduquiz: Classification of Living Organisms” to improve the learning outcomes of seventh-grade students. The background of this study is the lack of engaging digital media in junior high school science instruction, and the fact that many students’ learning outcomes have not yet met the minimum passing standard. The solution to the problems outlined in the background is the development of “Eduquiz: Classification of Living Organisms” to improve the learning outcomes of seventh-grade students. “Eduquiz: Classification of Living Organisms” was developed using the Scratch and Canva platforms to create engaging and interactive features and visuals. This study employed the Research and Development (R&D) method using the Four-D research model (Define, Design, Develop, Disseminate). Data were obtained from the results of validation tests by subject matter experts and media experts, as well as from pretest and posttest scores. The data analysis techniques used in this study were prerequisite analysis and hypothesis testing, which included normality tests, homogeneity tests, N-Gain score tests, and paired simple t-tests. The validity test results from the subject-matter expert validators showed an average of 85%, categorized as “valid,” while the results from the media expert validators showed an average of 72%, categorized as “sufficiently valid.” Additionally, the reliability test yielded a result of 0.90 > 0.70. The effectiveness test results indicate an improvement in performance before and after the use of the “Eduquiz: Classification of Living Organisms” learning media. This is evidenced by the N-Gain score test result of 0.34, categorized as moderate, and the paired-sample t-test yielding a sig (2-tailed) value of 0.000, which means rejecting H0 and accepting Ha. Therefore, it can be concluded that the “Classification of Living Organisms” Eduquiz is deemed valid and effective for use in the learning process to improve student learning outcomes.